Late Quaternary paleoceanography of the northern continental margin of Svalbard - Chauhan, Teena (UiT Norges arktiske universitet, 2015)
Paper II and III of this thesis are not available in Munin. Paper II: Paleoceanography of the Barents Sea continental margin, north of Nordaustlandet, Svalbard during the last 74 ka. Teena Chauhan, Tine L Rasmussen and Riko Noormets. (Manuscript). Published version available in Boreas, 17 Jul. 2015 Paper III: Glaciomarine sedimentation and bottom current activity along the north-western and northern continental margins of Svalbard during the late Quaternary. Teena Chauhan, Riko Noormets and Tine L Rasmussen. (Manuscript). Published version available in Geo-Marine Letters, 05 December 2015 This study focuses on the reconstruction of the variability of Atlantic Water inflow to the Arctic Ocean and its influence on the Svalbard-Barents Sea Ice Sheet (SBIS), sea-ice cover, variations in the bottom current strength and the depositional environment in the past. For this reconstruction, the distribution patterns of planktic and benthic foraminiferal assemblages, oxygen and carbon stable isotopes in planktic and benthic foraminifera, ice-rafted debris, grain size of the sediment in particular sortable silt, and organic carbon content from two sediment cores were investigated. The results show that variable strength of the subsurface Atlantic Water together with insolation has influenced the extent of the sea-ice cover and the stability of the SBIS since 132,000 years before present (Termination II). Besides, distinct increase in freshwater flux from melting of glacier ice during deglaciation periods at around 60,000 years (MIS 4/3) and between 19,000 and 11,500 years (MIS 2/1) also had significant influence on the oceanography through stratification of the upper water column and weakening of the ocean circulation. This led to poor ventilation at the sea bottom and expansion of sea-ice cover at the surface. The influence of these ‘climate drivers’ on the local sedimentary and oceanographic environment varied significantly. This emphasizes the importance of considering regional environmental parameters and feedback ...